Investigation of polarization in membrane distillation (MD) process and its energy efficient solution for freshwater production in Malaysian households - Bahar, Rubina; Ariff, Tasnim Firdaus; Ismail, Yusof (2017)
Recent water scarcity in Malaysia has raised an issue about the abundant supply of freshwater in the country. A water purification method like Membrane Distillation (MD) can be a wonderful solution to be utilized to deal with this immediate unpredictable water scarcity issues. MD is an ambient pressure process which works mostly below a temperature of 80 Degree Celsius, hence very much suitable to harvest solar/ waste energy. However, MD system has a limitation of restricted production due to temperature and concentration polarization on the membrane surface.This work aims to deal with fundamental investigation on Polarization in MD process to make it a more effective. freshwater supply system for Malaysian households. It has been observed that using smaller sized multiple chambers in the process can enhance the production of fresh water compared to a bigger sized chamber with a single large membrane. Association of solar heat into the MD module can contribute to further energy savings in the process and make it economical and feasible for water treatment in hot tropical climate. It has been observed that for using multi stage, a distilled water flux of 8.5 liter/m2h has been obtained.